Comment on Huma Tabassum, et al. (J Pak Med Assoc. 2024; 74(1): 10-15) Comparison of muscle energy technique and facet joint mobilisation in the patient with chronic neck pain: A randomized controlled trial - Muhammad Osama; Sabah Afridi (Journal of the Pakistan Medical Association, 2024)
The neck region stands out as the most common site for musculoskeletal symptoms, with neck pain ranking as the 4th leading cause of disability.1 The research paper published by Tabassum H et al on the management of neck pain, offers valuable insights into the effects of facet joint mobilization and Muscle Energy Techniques (MET), in the management of this prevalent and important condition. However, we would like to take this opportunity to present certain considerations; which may provide a more nuanced perspective regarding the effects and comparison of these interventions. Continued...